Online Flipped Classroom: Developing Postgraduate Science Education Students’ Critical Thinking Skills - Wahono Widodo (Universitas Pendidikan Indonesia, 2022)
During the Covid-19 pandemic, online learning should be carried out through innovative methods. This study aims to determine whether implementing an online flipped classroom, with converting all face-to-face sessions into virtual face-to-face sessions, can facilitate the development of critical thinking skills of postgraduate science education students in the School Physics course. This quantitative study used one group pretest-postest research design. The subjects were postgraduate science education students who took School Physics courses in the first semester at one of the public universities in Indonesia. Online Flipped classroom was supported by Google Classroom Learning Management System (LMS). Critical thinking skills data in School Physics were obtained through tests. Data were analyzed using a description of normalized changes (c) and nonparametric-inferential analysis with the Related-Samples Wilcoxon Signed Rank Test. The results showed that the online flipped classroom could facilitate the development of the students’ critical thinking skills with an average normalized change of .71 in a high category. Even though the students felt the benefits of an online flipped classroom, they still wanted a face-to-face learning mode to be carried out soon.